Positive electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery

CN116250100BActive Publication Date: 2026-10-27PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180066276.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-30
Filing Date
2021-09-14
Publication Date
2026-10-27
Estimated Expiration
2041-09-14

AI Technical Summary

Benefits of technology

[0010]根据本发明,对于非水电解质二次电池,能够提高容量且抑制DCR的增大。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116250100B_ABST
    Figure CN116250100B_ABST
Patent Text Reader

Abstract

The positive electrode for a nonaqueous electrolyte secondary battery includes a positive electrode current collector and a positive electrode mixture layer loaded on the positive electrode current collector. The positive electrode mixture layer includes a positive electrode active material, a binder, and a conductive agent. The positive electrode active material includes a composite oxide having a crystal structure of a layered rock-salt type, containing lithium and an element A other than lithium, the element A containing at least nickel, and an atomic ratio Ni / A of nickel to the element A being 0.8 or more and 1.0 or less. The binder includes a high-molecular binder having a three-dimensional network structure. A mass of the positive electrode mixture layer loaded on the positive electrode current collector per 1 m 2 of the positive electrode current collector is 280 g or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a positive electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery. Background Technology

[0002] Non-aqueous electrolyte secondary batteries, such as lithium-ion batteries, are used as power sources for electronic devices like mobile terminals and for vehicles like electric vehicles. The positive electrode is obtained, for example, by coating a positive electrode slurry containing a positive electrode active material and other positive electrode additives onto the surface of a positive electrode current collector, drying the coating, and calendering it to form a positive electrode additive layer. The positive electrode active material, for example, uses a composite oxide having a layered rock-salt type crystal structure and containing lithium and nickel.

[0003] For high capacity applications, increasing the amount of positive electrode paste coated on the positive electrode current collector and thus increasing the thickness of the positive electrode binder layer is effective. When the positive and negative electrodes are wound together to form an electrode assembly with a separator in between, increasing the thickness of the positive electrode binder layer can reduce the number of turns of the positive electrode, reduce the separator and positive electrode current collector that do not contribute to the capacity, and correspondingly increase the amount of active material filling (e.g., Non-Patent Literature 1).

[0004] Existing technical documents

[0005] Non-patent literature

[0006] Non-patent literature 1: Topics, "Introduction to the Activities of ABRI Co., Ltd."; FB Technical News, No. 74 (November 2018), page 34 Summary of the Invention

[0007] In non-aqueous electrolyte secondary batteries, when the loading of the positive electrode flux layer on the positive electrode current collector becomes quite large, the DC resistance (DCR) increases significantly. It is believed that this increase in DCR is due to the increased internal resistance of the positive electrode flux layer. Furthermore, it is thought that when the loading of the positive electrode flux layer becomes quite large, the thickness of the positive electrode flux layer increases accordingly, the electron conduction path becomes longer, and the current collection performance decreases.

[0008] In view of the above, one aspect of the present invention relates to a positive electrode for a non-aqueous electrolyte secondary battery, comprising: a positive electrode current collector and a positive electrode binder layer loaded on the positive electrode current collector, the positive electrode binder layer comprising: a positive electrode active material, a binder, and a conductive agent, the positive electrode active material comprising a composite oxide having a layered rock salt-type crystal structure, containing lithium and an element A other than lithium, the element A containing at least nickel, the atomic ratio of nickel to element A being Ni / A being 0.8 or more and 1.0 or less, the binder comprising a polymeric binder having a three-dimensional mesh structure, the binder being loaded on the positive electrode current collector layer per 1m2 The mass of the positive electrode compound layer is 280g or more.

[0009] In addition, another aspect of the present invention relates to a non-aqueous electrolyte secondary battery comprising: a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein the positive electrode is the positive electrode.

[0010] According to the present invention, for non-aqueous electrolyte secondary batteries, the capacity can be improved and the increase of DCR can be suppressed. Attached Figure Description

[0011] Figure 1 This is a schematic perspective view obtained by cutting out a portion of a non-aqueous electrolyte secondary battery according to one embodiment of the present invention. Detailed Implementation

[0012] Positive electrode for non-aqueous electrolyte secondary batteries

[0013] As one embodiment of the present invention, a positive electrode for a non-aqueous electrolyte secondary battery comprises: a positive electrode current collector and a positive electrode binder layer loaded on the positive electrode current collector. The positive electrode binder layer includes: a positive electrode active material, a binder, and a conductive agent. The positive electrode active material comprises a nickel-based composite oxide. That is, the composite oxide has a layered rock salt-type crystal structure, contains lithium (Li) and element A other than Li, element A contains at least nickel (Ni), and the atomic ratio of Ni to element A, Ni / A, is 0.8 or more and 1.0 or less. The binder comprises a polymeric binder (hereinafter also referred to as binder P) having a three-dimensional mesh structure. The positive electrode binder layer is thick. That is, the thickness of the positive electrode binder layer is large per 1m of positive electrode current collector. 2 The mass of the positive electrode mixture layer is over 280g.

[0014] By using a nickel-based composite oxide with a Ni / A ratio of 0.8 or higher in the positive electrode active material, the per 1m of the positive electrode current collector is increased. 2 By increasing the loading of the positive electrode compound layer to over 280g and increasing the thickness of the positive electrode compound layer, the rated capacity of the battery can be increased to a level that was previously impossible to achieve.

[0015] Furthermore, it is believed that by including a polymeric adhesive with a three-dimensional mesh structure in a thick positive electrode binder layer, the distribution of the conductive agent coexisting with the adhesive is improved, and the electron conduction pathway within the positive electrode binder layer develops into a highly three-dimensional structure, thus reducing the internal resistance of the positive electrode binder layer. The improved distribution of the conductive agent can be attributed to the excellent adhesion between the composite oxide particles and the conductive agent by the polymeric adhesive with the three-dimensional mesh structure within the positive electrode binder layer. Furthermore, the adhesion between the positive electrode binder layer and the positive electrode current collector is improved, thereby improving the resistance to stress associated with the expansion and contraction of the positive electrode active material during charging and discharging. Therefore, even with a thick positive electrode binder layer, the reduction in adhesion between the positive electrode binder layer and the positive electrode current collector can be suppressed. Based on the above, the increase in the battery's discharge rate (DCR) is suppressed, and cycle characteristics are improved. The effect of suppressing the increase in DCR under conditions of high positive electrode binder layer loading is specifically obtained when the polymeric adhesive has a three-dimensional mesh structure. For example, in the case of linear polymeric adhesives (e.g., polyvinylidene fluoride), the above-mentioned suppression of DCR increase is insufficient.

[0016] The adhesive P can be formed, for example, by crosslinking a polymer that acts as an adhesive. Crosslinking can be achieved using known methods such as adding a crosslinking agent, heating, ultraviolet light, or electron beam irradiation. From the viewpoint of electrochemical stability at a positive electrode potential, the adhesive P preferably contains a fluoropolymer that has been crosslinked. That is, it is preferable that the fluoropolymer with adhesive properties is crosslinked to form a three-dimensional mesh structure.

[0017] The fluoropolymer may contain at least one unit selected from the group consisting of units derived from vinylidene fluoride (VDF), units derived from hexafluoropropylene (HFP), and units derived from tetrafluoroethylene (TFE). In this case, the fluoropolymer itself exhibits excellent adhesive properties. From the viewpoint of electrochemical stability and the stability of the cathode slurry, the fluoropolymer preferably contains at least one unit derived from VDF. The fluoropolymer preferably contains at least one unit selected from the group consisting of polyvinylidene fluoride (PVDF) and copolymers containing units derived from vinylidene fluoride (VDF). The copolymer may be a block copolymer or a random copolymer.

[0018] The copolymer containing units derived from VDF may comprise a copolymer of VDF and a fluorinated monomer other than VDF (hereinafter referred to as monomer F). That is, the copolymer may contain units derived from VDF and units derived from monomer F. Monomer F may comprise at least one selected from the group consisting of HFP, TFE, ethylene trifluoride, and chlorotrifluoride. From the viewpoint of ensuring the flexibility of the positive electrode plate, monomer F is preferably HFP. In the copolymer, the molar ratio of units derived from monomer F to units derived from VDF (monomer F / VDF) may, for example, be 0.01 or more and 0.5 or less, or 0.05 or more and 0.3 or less.

[0019] Fluoropolymers can be crosslinked using crosslinking monomers (crosslinking agents). For example, fluoropolymers can undergo dehydration condensation reactions with crosslinking monomers to form amide or ester bonds, thereby crosslinking the fluoropolymers with each other via the crosslinking monomer. Crosslinking monomers can have functional groups (e.g., hydroxyl, carboxyl, amino, etc.) that contribute to the condensation reaction. Specific examples of crosslinking monomers include trimethylhexamethylenediamine, benzoyl peroxide, dicumyl peroxide, bisphenol A, hexamethylenediamine, ethylenediamine, isopropyl ethylenediamine, naphthyldiamine, 2,4,4-trimethyl-1 or 6-hexanediamine, etc. Fluoropolymers can have functional groups (e.g., hydroxyl, carboxyl, amino, etc.) that contribute to the dehydration condensation reaction with crosslinking monomers, or these functional groups can be introduced into the fluoropolymer. For example, a fluoropolymer with introduced carboxyl groups can undergo a dehydration condensation reaction with a crosslinking monomer having two amino groups, thereby crosslinking the fluoropolymers with each other via the crosslinking monomer using amide bonds.

[0020] The average molecular weight of the fluoropolymers (e.g., PVDF, PVDF-HFP) used with the above crosslinking agents is, for example, 100,000 or more and 2,000,000 or less. It should be noted that the above average molecular weight is a number-average molecular weight (converted to polystyrene) obtained by gel permeation chromatography (GPC).

[0021] The adhesive contains at least adhesive P. Adhesive P may constitute 50% or more by mass of the total adhesive, or it may be the entirety of the adhesive. The adhesive may contain small amounts of other components besides adhesive P. These other components may be resin materials that do not have a three-dimensional mesh structure (e.g., fluoropolymers, polyolefin resins, acrylic resins, etc.). Specific examples include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyethylene, polypropylene, polyacrylic acid, polymethyl acrylate, ethylene-acrylic acid copolymers, etc. Adhesive P and other components may be used individually or in combination.

[0022] The binder content in the positive electrode binder layer is preferably 0.5 parts by mass or more and 2 parts by mass or less relative to 100 parts by mass of the positive electrode active material. In this case, the capacity is improved and the suppression of DCR increase is easily obtained even with a large loading of the positive electrode binder layer. In addition, the adhesion strength of the positive electrode binder layer and the adhesion strength between the positive electrode binder layer and the positive electrode current collector are also easily improved. In this case, all of the binder can also be binder P.

[0023] From the perspective of improving high capacity and cycle characteristics, every 1m of positive electrode current collector... 2 The loading of the positive electrode additive layer can be 280g or more and 400g or less, or 280g or more and 360g or less. In this case, the thickness of the positive electrode additive layer is, for example, 50μm or more and 250μm or less.

[0024] The density of the positive electrode mixture layer can be 3.45 g / cm³. 3 Above and 3.75g / cm 3 The following can also be 3.5 g / cm³. 3 Above and 3.75g / cm 3 The density of the positive electrode binder layer is 3.45 g / cm³. 3 In the above cases, the number of contact points between the composite oxide and the conductive agent and binder increases. Furthermore, it is easier to form sufficient contact points between the composite oxide particles. This allows for the formation of sufficient electron conduction pathways, making it easier to obtain high capacity. Additionally, the adhesion strength of the positive electrode binder layer and the bonding strength between the positive electrode binder layer and the positive electrode current collector are also easily improved. Moreover, in the above cases, it is advantageous for improving the energy density of cylindrical batteries, etc., and is effective when using longer electrode plates to construct wound electrode assemblies.

[0025] The density of the positive electrode binder layer is 3.75 g / cm³. 3 Under the following conditions, the increased deformation within the positive electrode flux layer, which accompanies the expansion and contraction of the composite oxide during charging and discharging, is suppressed. This easily reduces the stress generated between the positive electrode flux layer and the positive electrode current collector, and effectively suppresses the decrease in the adhesion between them. Furthermore, within the positive electrode flux layer, the composite oxide readily contacts the non-aqueous electrolyte, suppressing the increase in reaction resistance. By appropriately ensuring porosity within the positive electrode flux layer, even at high charge rates, the diffusion resistance relative to the non-aqueous electrolyte (lithium ion movement) is sufficiently reduced, facilitating the attainment of high discharge capacity.

[0026] The positive electrode active material contains at least the aforementioned nickel-based composite oxides. When the atomic ratio (Ni / A) of the nickel-based composite oxide is 0.8 or higher, the proportion of Ni in element A is large, facilitating high capacity. The proportion of nickel-based composite oxides in the overall positive electrode active material is, for example, 80% by mass or higher, or the entire positive electrode active material may be composed of nickel-based composite oxides. The positive electrode active material may contain small amounts of other composite oxides besides nickel-based composite oxides (e.g., LiCoO2, Li2NiO2, Li5FeO4, etc.).

[0027] Element A contains at least Ni, and may further contain at least one selected from the group consisting of cobalt (Co), manganese (Mn), aluminum (Al), magnesium (Mg), calcium (Ca), iron (Fe), copper (Cu), zinc (Zn), chromium (Cr), titanium (Ti), niobium (Nb), zirconium (Zr), vanadium (V), tantalum (Ta), molybdenum (Mo), tungsten (W), strontium (Sr), silicon (Si), and boron (B).

[0028] Element A preferably contains Ni and at least one selected from the group consisting of Co, Mn, and Al, more preferably contains Ni and Co and contains Mn and / or Al. When element A contains Co, the phase transition of the composite oxide containing Li and Ni is suppressed during charge and discharge, improving the stability of the crystal structure and easily improving cycle characteristics. When element A contains Mn and / or Al, thermal stability is improved.

[0029] Nickel-based composite oxides are preferably made of the general formula Li a Ni x Co y M 1-x-y The oxide is shown in O2. Wherein, 0.97≤a≤1.2, 0.8≤x≤1.0 and 0≤y≤0.2, and M is preferably selected from at least one of the group consisting of Mn, Al, B, W, Sr, Mg, Mo, Nb, Ti, Si and Zr.

[0030] When the 'a' value, representing the Li composition ratio, is 0.97 or higher and 1.2 or lower, it is difficult to generate cation mixing where Ni ions enter Li sites, thus easily improving output characteristics. When the 'x' value, representing the Ni composition ratio, is 0.8 or higher and 1 or lower, Ni accounts for a large proportion of element A, making it easy to achieve high capacity. 'y' can be greater than 0 but less than 0.2. In this case, the inclusion of Co in the nickel-based composite oxide easily improves the stability of the crystal structure and the cycling characteristics. Element M can be Al, or it can be 0 < y ≤ 0.2, 0 < (1-xy) ≤ 0.05. In this case, the inclusion of Al in the nickel-based composite oxide easily improves the thermal stability of the composite oxide. It should be noted that the value of 'a' changes during charge and discharge.

[0031] The particles of composite oxides typically comprise secondary particles formed by the aggregation of multiple primary particles. The average particle size (D50) of these secondary particles is, for example, greater than 5 μm and less than 20 μm. It should be noted that the average particle size (D50) referred to here is the median particle size at which the cumulative volumetric value in a volumetric particle size distribution reaches 50%. The average particle size (D50) of the secondary particles is determined by particle size distribution measurement using laser diffraction.

[0032] By including a conductive agent in the positive electrode binder layer, sufficient conductive pathways are formed between the positive electrode active materials and between the positive electrode active materials and the positive electrode current collector. The conductive agent preferably comprises carbon nanotubes (CNTs). CNTs readily entangle with a three-dimensional mesh-structured polymer binder, which firmly maintains the contact points between the CNTs and the composite oxide during charging and discharging.

[0033] The average length of the CNTs is preferably 0.5 μm or more, more preferably 0.5 μm or more and 10.0 μm or less, and even more preferably 0.5 μm or more and 5.0 μm or less. In this case, the CNTs are more easily entangled with the polymer adhesive with a three-dimensional mesh structure, and the polymer adhesive easily and firmly maintains the contact points between the CNTs and the composite oxide during charging and discharging. In addition, the CNTs are easily present between the composite oxide particles, and the CNTs can easily and sufficiently form electronic conduction pathways between the composite oxide particles.

[0034] From the perspective of improving cycle performance, the average diameter of CNTs can be 0.5 nm or more and 30 nm or less, or 0.5 nm or more and 20 nm or less. When the average diameter of CNTs is 0.5 nm or more, the strength of the CNTs is sufficiently ensured, and electron conduction pathways are easily maintained through the CNTs during charge and discharge. Furthermore, CNTs tend to exist between composite oxide particles.

[0035] The average length and average diameter of CNTs are calculated as follows: A cross-sectional image of the positive electrode mixture layer or the CNTs is obtained using a scanning electron microscope (SEM) or a transmission electron microscope (TEM). Using this image, multiple CNTs (e.g., approximately 50 to 200) are randomly selected to measure their length and diameter, and then averaged to obtain the values. It should be noted that the length of the CNT refers to its length when it is in a straight line.

[0036] Conductive agents can include conductive materials other than CNTs. Examples of conductive materials other than CNTs include natural graphite, artificial graphite, etc.; carbon black such as acetylene black; metal fibers; and metal powders such as aluminum. Conductive agents can be used alone or in combination of two or more.

[0037] The content of the conductive agent in the positive electrode mixture layer is preferably, for example, 0.01 parts by mass or more and 1.0 parts by mass or less relative to 100 parts by mass of the positive electrode active material. In this case, the capacity is improved and the electron conduction pathway between the positive electrode active material particles is easily and sufficiently formed by the conductive agent. In this case, all of the conductive agent may also be CNTs.

[0038] For example, a non-porous conductive substrate (metal foil, etc.) or a porous conductive substrate (mesh, mesh, perforated sheet, etc.) can be used as the positive current collector. Examples of materials for the positive current collector include stainless steel, aluminum, aluminum alloy, and titanium. The thickness of the positive current collector is, for example, 3–50 μm.

[0039] The manufacturing method of the positive electrode includes, for example, the following steps: preparing a positive electrode slurry by dispersing a positive electrode mixture containing a positive electrode active material, a binder, and a conductive agent in a dispersion medium; and coating the positive electrode slurry onto the surface of the positive electrode current collector and drying it to form a positive electrode mixture layer. The dried coating can also be calendered as needed. The positive electrode mixture layer can be formed on one surface or on both surfaces of the positive electrode current collector. As a dispersion medium, for example, water, alcohols such as ethanol, and N-methyl-2-pyrrolidone (NMP) can be used.

[0040] [Non-aqueous electrolyte secondary battery]

[0041] One embodiment of the present invention includes: a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode uses the aforementioned non-aqueous electrolyte positive electrode for secondary batteries.

[0042] The negative electrode, for example, comprises: a negative electrode current collector and a negative electrode additive layer loaded on the negative electrode current collector. The negative electrode is obtained, for example, by coating a negative electrode slurry, in which a negative electrode additive is dispersed in a dispersion medium, onto the surface of the negative electrode current collector, drying it, and forming the negative electrode additive layer. The dried coating can also be calendered as needed. The negative electrode additive layer can be formed on one surface or on both surfaces of the negative electrode current collector. The negative electrode additive contains a negative electrode active substance as a necessary component, and as an arbitrary component, it can contain binders, conductive agents, thickeners, etc. As a binder, other components besides the aforementioned binder P, rubber materials such as styrene-butadiene rubber, etc., can be used. As a dispersion medium, examples of the positive electrode can be used. Furthermore, as a conductive agent, examples of the positive electrode can also be used besides graphite. As a thickener, for example, carboxymethyl cellulose (CMC) and its modified forms (including salts such as sodium salts) can be used.

[0043] Examples of anode active materials include carbon materials, silicon, silicon-containing materials, and lithium alloys.

[0044] From the perspective of increasing capacity, the negative electrode active material is preferably a Si-based active material containing at least one of silicon and a silicon-containing material. As the silicon-containing material, for example, a composite material can be used, which includes: a silicate phase containing at least one of an alkali metal element and a Group 2 element, and silicon particles dispersed in the silicate phase. In this case, the initial charge-discharge efficiency and cycle characteristics are improved. The composite material includes, for example, a lithium silicate phase and silicon particles dispersed in the lithium silicate phase. The lithium silicate phase may have, for example, Li 2u SiO u+2 a composition represented by (0<u<2). As the silicon-containing material, SiO including a SiO2 phase and silicon particles dispersed in the SiO2 phase can be used z (0.5≤z≤1.5). The surfaces of the particles of the silicon-containing material may also be covered with a conductive layer containing a conductive material such as a carbon material.

[0045] Examples of the carbon material include graphite, graphitizable carbon (soft carbon), non-graphitizable carbon (hard carbon), and the like. Among them, graphite is preferred, which has excellent charge-discharge stability and low irreversible capacity. Graphite refers to a material having a graphite-type crystal structure, and includes, for example, natural graphite, artificial graphite, graphitized mesophase carbon particles, and the like. The carbon material may be used alone, or two or more types may be used in combination.

[0046] From the viewpoint of easily obtaining good cycle characteristics and high capacity in a balanced manner, it is preferable to use the Si-based active material and the carbon material in combination. From the perspective of increasing capacity, the proportion of the Si-based active material in the total of the Si-based active material and the carbon material is, for example, preferably 0.5 mass% or more, more preferably 1 mass% or more, and further preferably 2 mass% or more. In addition, from the viewpoint of improving cycle characteristics, the proportion of the Si-based active material in the total of the Si-based active material and the carbon material is, for example, preferably 30 mass% or less, more preferably 20 mass% or less, and further preferably 15 mass% or less.

[0047] For the negative electrode current collector sheet, for example, the conductive substrate exemplified for the positive electrode can be used. Examples of the material of the negative electrode current collector sheet include stainless steel, nickel, nickel alloys, copper, copper alloys, and the like. The thickness of the negative electrode current collector sheet is, for example, 1 to 50 μm.

[0048] The non-aqueous electrolyte includes a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.

[0049] As a non-aqueous solvent, cyclic carbonates, chain carbonates, cyclic carboxylic acid esters, and chain carboxylic acid esters can be used, for example. Examples of cyclic carbonates include propylene carbonate (PC) and ethylene carbonate (EC). Cyclic carbonates with unsaturated bonds, such as vinylene carbonate (VC), can also be used. Cyclic carbonates with fluorine atoms, such as fluoroethylene carbonate (FEC), can also be used. Examples of chain carbonates include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). Examples of cyclic carboxylic acid esters include γ-butyrolactone (GBL) and γ-valerolactone (GVL). Examples of chain carboxylic acid esters include methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, and propyl propionate. One non-aqueous solvent can be used alone, or two or more can be used in combination.

[0050] Examples of lithium salts include LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiCF3CO2, LiAsF6, and LiB. 10 Cl 10 Examples of borates include lower aliphatic carboxylic acids such as lithium, LiCl, LiBr, LiI, borates, and imide salts. Examples of borates include lithium bis(1,2-phenylene glycolate (2-)-O,O'), lithium bis(2,3-naphthalene glycolate (2-)-O,O'), lithium bis(2,2'-biphenylene glycolate (2-)-O,O'), and lithium bis(5-fluoro-2-olate-1-benzenesulfonic acid-O,O'). Examples of lithium salts include lithium bis(fluorosulfonyl)imide (LiN(FSO2)2), lithium bis(trifluoromethanesulfonate)imide (LiN(CF3SO2)2), lithium trifluoromethanesulfonate nonafluorobutanesulfonate imide (LiN(CF3SO2)(C4F9SO2)), and lithium bis(pentafluoroethanesulfonate)imide (LiN(C2F5SO2)2). A single lithium salt can be used alone, or in combination of two or more. The concentration of lithium salts in non-aqueous electrolytes is, for example, 0.5 mol / L or more and 2 mol / L or less.

[0051] Typically, a separator is preferably sandwiched between the positive and negative electrodes. The separator has high ion permeability, appropriate mechanical strength, and insulation properties. Microporous membranes, woven fabrics, non-woven fabrics, etc., can be used as separators. Polyolefins such as polypropylene and polyethylene are preferred materials for the separator.

[0052] As an example of the structure of a non-aqueous electrolyte secondary battery, a structure in which the positive and negative electrodes are wound together with a separator, and the non-aqueous electrolyte is housed in a casing. Alternatively, instead of a wound electrode assembly, other electrode assemblies such as a stacked electrode assembly in which the positive and negative electrodes are separated by a separator can be used. Non-aqueous electrolyte secondary batteries can be of any shape, such as cylindrical, square, coin-shaped, button-shaped, or laminated.

[0053] Figure 1 This is a schematic perspective view obtained by cutting out a portion of a non-aqueous electrolyte secondary battery according to one embodiment of the present invention.

[0054] The battery comprises: a square-shaped battery casing 4, an electrode assembly 1 housed within the battery casing 4, and a non-aqueous electrolyte. The electrode assembly 1 has: a strip-shaped negative electrode, a strip-shaped positive electrode, and a separator sandwiched between them to prevent direct contact. The electrode assembly 1 is formed by winding the negative electrode, positive electrode, and separator around a flat core, and then pulling out the core.

[0055] One end of the negative electrode lead 3 is mounted to the negative electrode current collector via welding or the like. The other end of the negative electrode lead 3 is electrically connected to the negative terminal 6 provided on the sealing plate 5 via a resin insulating plate. The negative terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. One end of the positive electrode lead 2 is mounted to the positive electrode current collector via welding or the like. The other end of the positive electrode lead 2 is connected to the back of the sealing plate 5 via an insulating plate. That is, the positive electrode lead 2 is electrically connected to the battery casing 4, which also serves as the positive terminal. The insulating plate isolates the electrode assembly 1 from the sealing plate 5, and also isolates the negative electrode lead 3 from the battery casing 4. The periphery of the sealing plate 5 fits into the open end of the battery casing 4, and the fitting part is laser welded. In this way, the opening of the battery casing 4 is sealed by the sealing plate 5. The injection hole for the non-aqueous electrolyte provided on the sealing plate 5 is blocked by a plug 8.

[0056] [Example]

[0057] The present invention will now be described in detail based on the embodiments, but the present invention is not limited to the following embodiments.

[0058] Example 1

[0059] (Preparation of composite oxides)

[0060] Ni obtained by co-precipitation method 0.8 Co 0.17 Al 0.03 (OH)₂ and Li₂CO₃ were mixed such that the atomic ratio of Li relative to the total atomic ratio of Ni, Co, and Al (Li / (Ni+Co+Al)) was 1.05 / 1, and then calcined under an oxygen atmosphere to obtain a composite oxide. The composition of the obtained composite oxide is Li₂.1.05 Ni 0.8 Co 0.17 Al 0.03 O2 (Ni / A = 0.8). It should be noted that the composition of the composite oxide was determined by ICP emission spectroscopy analysis. By using pulverization and sieving, a composite oxide powder with an average particle size of 12 μm was obtained.

[0061] (Preparation of cross-linked fluoropolymers)

[0062] A copolymer of vinylidene fluoride and hexafluoropropylene, PVDF-HFP (manufactured by Sigma-Aldrich), and trimethylhexamethylenediamine (manufactured by Tokyo Chemical Industry Co., Ltd.) as a crosslinking agent were dissolved in methyl isobutyl ketone to obtain a mixed solution. A film was prepared by casting the mixed solution (solution casting method). The film was heated at 110°C to produce a crosslinked fluoropolymer (adhesive P). The amount of trimethylhexamethylenediamine added was 0.1 parts by weight relative to 100 parts by weight of PVDF-HFP. The film-like adhesive P was pulverized into a powder.

[0063] To confirm the three-dimensional crosslinking, DMA (Dynamic Mechanical Analysis), DSC (Differential Scanning Calorimetry), and EGA (Evolved Gas Analysis) were performed. DMA confirmed the storage modulus, demonstrating a high storage modulus due to the three-dimensional crosslinking. DSC confirmed an increase in the glass transition temperature (Tg) of the PVDF polymer. EGA confirmed a shift in the peak origin temperature of the VDF-derived 1,3,5-trifluorobenzene at m / z = 132 towards higher temperatures. These analyses confirmed that the obtained crosslinked fluoropolymer possesses a three-dimensional mesh structure of PVDF-HFP crosslinking.

[0064] (The production of the positive electrode)

[0065] A positive electrode slurry was prepared by adding 1 part by weight of binder, 1 part by weight of conductive agent, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) to 100 parts by weight of positive electrode active material and stirring. The positive electrode active material used was the composite oxide prepared above. The binder used was the cross-linked fluoropolymer prepared above. The conductive agent used was carbon nanofibers (average length 1 μm, average diameter 10 nm).

[0066] A positive electrode paste is coated onto the surface of an aluminum foil (positive current collector). After the coating dries, it is calendered to form a positive electrode mixture layer (density 3.5 g / cm³) on both sides of the aluminum foil. 3Thus, the positive electrode is obtained. At this point, with each 1m of the positive electrode current collector... 2 The loading of the positive electrode additive layer was adjusted to 280g to control the coating amount of the positive electrode slurry.

[0067] (Making the negative electrode)

[0068] Add 1 part by mass of styrene-butadiene rubber (SBR), 1 part by mass of sodium carboxymethyl cellulose (CMC-Na), and an appropriate amount of water to 100 parts by mass of negative electrode active material, and stir to prepare negative electrode slurry.

[0069] The negative electrode active material uses a mixture of Si-containing material and graphite (average particle size (D50) 25 μm). The mass ratio of Si-containing material to graphite in the negative electrode active material is 10:90. The Si-containing material uses SiO₂ with a surface covered by a conductive layer containing conductive carbon. x Particles (x = 1, average particle size (D50) 5 μm). Relative to SiO₂ x The total mass of particles and conductive layer is 100 parts by mass, and the coverage of conductive layer is 5 parts by mass.

[0070] A negative electrode paste is coated onto the surface of a copper foil (negative electrode current collector). After the coating dries, it is rolled to form a negative electrode mixture layer (200 μm thick, 1.4 g / cm³) on both sides of the copper foil. 3 In this way, a negative electrode is obtained.

[0071] (Preparation of non-aqueous electrolytes)

[0072] LiPF6 was dissolved at a concentration of 1.0 mol / L in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio 3:7) to obtain a non-aqueous electrolyte.

[0073] (Fabrication of a non-aqueous electrolyte secondary battery)

[0074] An aluminum positive electrode lead is attached to one end of the positive electrode obtained above. A nickel negative electrode lead is attached to one end of the negative electrode obtained above. A wound electrode assembly is fabricated by winding the positive and negative electrodes using a polyethylene separator. After vacuum drying the electrode assembly at 105°C for 2 hours, it is housed in a bottomed cylindrical battery casing that also serves as the negative terminal. The battery casing is made of iron (18 mm outer diameter, 65 mm height). Next, a non-aqueous electrolyte is injected into the battery casing, and the opening of the battery casing is sealed using a metal seal that also serves as the positive terminal. At this time, a resin gasket is sandwiched between the seal and the opening of the battery casing. The other end of the positive electrode lead is connected to the seal, and the other end of the negative electrode lead is connected to the inner bottom surface of the battery casing. This fabricates a cylindrical non-aqueous electrolyte secondary battery (battery A1) of type 18650.

[0075] The following evaluation is given to battery A1.

[0076] [Evaluation 1: Initial Capacity]

[0077] For the aged battery, it was charged at a constant current of 0.5C (1800mA) until the voltage reached 4.2V, then charged at a constant voltage of 4.2V until the current reached 0.05C (180mA). Then, it was discharged at a constant current of 0.1C until the voltage reached 2.5V; this discharge capacity was set as the initial capacity. The pause time between charging and discharging was set to 10 minutes. Charging and discharging were performed at 25°C. The initial capacity is expressed as an index of 100 for the initial capacity of battery B1.

[0078] [Evaluation 2: Circulatory Capacity Maintenance]

[0079] Charge-discharge cycle tests were conducted under the following conditions. The pause between charging and discharging was set to 10 minutes. Charge and discharge were performed at 25°C.

[0080] <Charge>

[0081] Charge at a constant current of 0.5C (1800mA) until the voltage reaches 4.2V, then charge at a constant voltage of 4.2V until the current reaches 0.05C (180mA).

[0082] <Discharge>

[0083] Perform constant current discharge at 0.5C until the voltage reaches 2.5V.

[0084] Under the above conditions, repeated charging and discharging were performed. The ratio (percentage) of the discharge capacity in the 100th cycle to the discharge capacity in the 1st cycle was used to calculate the cycle capacity retention rate (%). The cycle capacity retention rate was expressed as an exponent with the cycle capacity retention rate of battery B1 set to 100.

[0085] [Evaluation 3: DC Resistance (DCR)]

[0086] Under the same conditions as evaluation 2 above, the charge-discharge cycle was repeated twice. For the battery after the second discharge cycle, it was charged at a constant current of 0.2C (720mA) at 25°C until the voltage reached 4.2V, and then charged at a constant voltage of 4.2V until the current reached 0.02C (72mA). In this way, a battery with a fully charged state (SOC 100%) was obtained.

[0087] For a fully charged battery, a constant current I is applied for discharge. The difference ΔV between the voltage just before discharge begins and the voltage 10 seconds after discharge begins is calculated. ΔV is divided by the current I (ΔV / I) to obtain the DC resistance (Ω). The DC resistance (DCR) is expressed as the exponent with the DCR of battery B1 set to 100.

[0088] Example 2

[0089] To make every 1m of the positive electrode current collector 2 The coating amount of the positive electrode slurry was adjusted to 330g by loading the positive electrode agent layer. Otherwise, the battery A2 of Example 2 was made and evaluated by the same method as the battery A1 of Example 1.

[0090] Comparative Examples 1 and 3

[0091] PVDF-HFP is used in the adhesive to ensure that each 1m of the positive electrode current collector... 2 The coating amount of the positive electrode slurry was adjusted to the values ​​shown in Table 1, with the loading amount of the positive electrode additive layer as described above. In addition to the above, batteries B1 and B3 of Comparative Examples 1 and 3 were prepared and evaluated using the same method as battery A1 of Example 1.

[0092] Comparative Example 2

[0093] PVDF-HFP was used in the adhesive. Otherwise, the battery B3 of Comparative Example 3 was prepared and evaluated using the same method as the battery A1 of Example 1.

[0094] Comparative Example 4

[0095] A cross-linked fluoropolymer was used in the adhesive. Otherwise, the battery B4 of Comparative Example 4 was prepared and evaluated using the same method as battery B1 of Comparative Example 1.

[0096] Comparative Example 5

[0097] LiCoO2 (Ni / A = 0) was used as the positive electrode active material. Otherwise, the battery B5 of Comparative Example 5 was prepared and evaluated using the same method as the battery A1 of Example 1.

[0098] The evaluation results of batteries A1 to A2 and batteries B1 to B5 are shown in Table 1.

[0099] [Table 1]

[0100]

[0101] Among batteries A1 to A2, the DCR is small, the initial capacity is large, and excellent cycle characteristics are obtained.

[0102] In battery B1, the loading of the positive electrode binder layer is low, resulting in a reduced initial capacity. In batteries B2-B3, the loading of the positive electrode binder layer is increased, but the use of PVDF-HFP in the binder leads to an increased DCR and reduced cycle performance. In battery B4, a cross-linked fluoropolymer is used in the binder, but the initial capacity is still reduced due to the low loading of the positive electrode binder layer. In battery B5, the initial capacity is reduced due to the use of LiCoO2 in the positive electrode active material.

[0103] Examples 3-5

[0104] The compression of the dried coating was adjusted to achieve the density of the positive electrode binder layer as shown in Table 2. Otherwise, batteries A3 to A5 of Examples 3 to 5 were prepared using the same method as battery A1 of Example 1 and evaluated. The evaluation results of batteries A3 to A5 are shown in Table 2. Table 2 also shows the evaluation results of battery A1.

[0105] [Table 2]

[0106]

[0107] Batteries A1, A3-A5 all exhibit low DCR and high initial capacity, resulting in excellent cycle characteristics. Particularly noteworthy is the positive electrode flux layer density of 3.45 g / cm³. 3 Above and 3.75g / cm 3 In the following batteries A1 and A4, the DCR is further reduced and the cycle characteristics are further improved.

[0108] Examples 6-8

[0109] CNTs with an average length as shown in Table 3 were used in the conductive agent. Otherwise, batteries A6 to A8 of Examples 6 to 8 were fabricated and evaluated using the same method as battery A1 of Example 1. The evaluation results of batteries A6 to A8 are shown in Table 3. Table 3 also shows the evaluation results of battery A1.

[0110] [Table 3]

[0111]

[0112] Batteries A1, A6 to A8 all exhibit low DCR and high initial capacity, resulting in excellent cycle characteristics. In particular, batteries A1, A7 to A8 with an average CNT length of 0.5 μm or more show further reductions in DCR and further improvements in cycle characteristics.

[0113] Industrial availability

[0114] The positive electrode for non-aqueous electrolyte secondary batteries of the present invention is suitable, for example, for non-aqueous electrolyte secondary batteries requiring high capacity and excellent cycle characteristics.

[0115] Explanation of reference numerals in the attached figures

[0116] Electrode group 1

[0117] 2 Positive leads

[0118] 3 negative leads

[0119] 4 Battery casing

[0120] 5 sealing boards

[0121] 6 negative extremes

[0122] 7 gaskets

[0123] 8 seals

Claims

1. A wound-type non-aqueous electrolyte secondary battery, comprising: a wound electrode assembly containing a positive electrode and a negative electrode, and a non-aqueous electrolyte. The positive electrode comprises: a positive current collector and a positive electrode flux layer loaded on the positive current collector. The positive electrode mixture layer comprises: a positive electrode active material, a binder, and a conductive agent. The positive electrode active material comprises a composite oxide having a layered rock salt-type crystal structure and containing lithium and element A other than lithium. Element A contains at least nickel. The atomic ratio of nickel to element A, Ni / A, is 0.8 or higher and 1.0 or lower. The adhesive comprises a polymeric adhesive with a three-dimensional mesh structure. The polymeric adhesive comprises a fluoropolymer. The fluoropolymer is cross-linked using cross-linking monomers. The fluoropolymer forms amide or ester bonds with the crosslinking monomer. The conductive agent contains carbon nanotubes. The carbon nanotubes have an average length of 0.5 μm or more and 10.0 μm or less. Within the positive electrode binder layer, the carbon nanotubes are entangled with a polymer adhesive having a three-dimensional mesh structure. Loaded on each 1m of the positive current collector 2 The mass of the positive electrode mixture layer is more than 280g. The density of the positive electrode mixture layer is 3.45 g / cm³. 3 Above and 3.75g / cm 3 the following.

2. The wound-type non-aqueous electrolyte secondary battery according to claim 1, wherein, The composite oxide is composed of the general formula Li a Ni x Co y M 1-x-y O2 indicates that In the formula, 0.97≤a≤1.2, 0.8≤x≤1.0 and 0≤y≤0.2, and M is at least one selected from the group consisting of Mn, Al, B, W, Sr, Mg, Mo, Nb, Ti, Si and Zr.

3. The wound-type non-aqueous electrolyte secondary battery according to claim 1, wherein, The fluoropolymer comprises at least one selected from the group consisting of polyvinylidene fluoride and copolymers containing units derived from polyvinylidene fluoride.

4. The wound-type non-aqueous electrolyte secondary battery according to claim 3, wherein, The copolymer containing units derived from vinylidene fluoride comprises copolymers of vinylidene fluoride and fluorinated monomers other than vinylidene fluoride. The fluorinated monomers other than vinylidene fluoride include at least one selected from the group consisting of propylene hexafluoride, ethylene tetrafluoride, ethylene trifluoride, and ethylene trifluoride chloride.

Citation Information

Patent Citations

  • Slurry for electrode mixture of lithium secondary cell, electrode using the slurry, and lithium secondary cell

    CN102473916A

  • Positive electrode for non-aqueous electrolyte lithium secondary battery and manufacture thereof

    JP1996031408A

  • Electrode for battery, and secondary battery

    JP1997097611A

  • Positive electrode material for lithium ion secondary battery, positive electrode active material layer, and lithium ion secondary battery

    WO2019168035A1